2014
DOI: 10.3851/imp2953
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of NKG2C+ Natural Killer Cells, TLR-2 Expression on Monocytes and Downregulation of Regulatory T-Cells Influence PEG-IFN Treatment Efficacy in Entecavir-Suppressed Patients with CHB

Abstract: Successful response to PEG-IFN-α correlates with an early significant restoration of impaired immune responses. Although antiviral treatment response can be achieved by both IFN and ETV, the underlying immunological features vary which may explain the generally observed difference in off-treatment durability of response between the two treatments, as well as effects on HBsAg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Recently, NKG2C + NK cells promoting a memory‐like response to certain viruses have been elucidated . We previously reported that a successful response to PegIFNα was associated with significant restoration of impaired immune responses manifested by decreased proportions and diminished inhibitory function of Tregs, increased proportions of NKG2C + NK cells, and higher proportions of TLR2 + CD14 + monocytes . These data suggested that modulating the number or function of Tregs, NK cells and monocytes in interferon‐based treatment may facilitate higher HBsAg clearance or clinical cure of HBV chronic infection through restoration of a robust immune response during anti‐HBV treatment.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Recently, NKG2C + NK cells promoting a memory‐like response to certain viruses have been elucidated . We previously reported that a successful response to PegIFNα was associated with significant restoration of impaired immune responses manifested by decreased proportions and diminished inhibitory function of Tregs, increased proportions of NKG2C + NK cells, and higher proportions of TLR2 + CD14 + monocytes . These data suggested that modulating the number or function of Tregs, NK cells and monocytes in interferon‐based treatment may facilitate higher HBsAg clearance or clinical cure of HBV chronic infection through restoration of a robust immune response during anti‐HBV treatment.…”
Section: Discussionmentioning
confidence: 96%
“…In the OSST study, switching to 48 weeks of PegIFNα treatment from ETV significantly increased HBeAg seroconversion rate and HBsAg loss in CHB patients who had a long‐term ETV treatment with sustained HBV DNA suppression . Moreover, PegIFNα responders showed a significantly higher increase in the NKG2C + NK cell proportions from baseline to week 12 . But the detailed immunomodulation role of NK cells in HBV clearance has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…The numbers and functions of Tregs and DCs are restored to normal levels after NA treatment (26,27). Thirdly, natural killer cell characteristics in CHB patients are associated with HBsAg clearance (28). Combination treatment with PEG-IFNα and ADV significantly influences NK-cell function (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…47 This has been further demonstrated where Peg-IFNα add-on was employed in patients virally suppressed with ETV, resulting in a reduction in T-reg frequencies with an increase in NKG2C+ NK cells and TLR-2+ CD14 monocytes, which was associated with treatment response. 94 In the same cohort, the expansion of CD56 bright NK cells expressing activatory receptors NKp30 and NKp46 along with TRAIL and IFNγ correlated with HBsAg decline with potential cccDNA clearance through TRAILinduced cytolysis, demonstrating the importance of Peg-IFNα for immune modulation and HBV clearance. 95 Similarly, in patients primed with Peg-IFNα prior to viral suppression, the maintenance of expanded functional CD56 bright NK cells has been shown to correlate with treatment response.…”
Section: Nucleos(t)ide Analoguesmentioning
confidence: 85%
“…Viral load reduction is able to maintain the immune stimulatory effects of Peg‐IFNα, when administered in combination or sequence, compared to Peg‐IFNα alone, which implies there may be beneficial outcomes with add‐on or combination therapies . This has been further demonstrated where Peg‐IFNα add‐on was employed in patients virally suppressed with ETV, resulting in a reduction in T‐reg frequencies with an increase in NKG2C+ NK cells and TLR‐2+ CD14 monocytes, which was associated with treatment response . In the same cohort, the expansion of CD56 bright NK cells expressing activatory receptors NKp30 and NKp46 along with TRAIL and IFNγ correlated with HBsAg decline with potential cccDNA clearance through TRAIL‐induced cytolysis, demonstrating the importance of Peg‐IFNα for immune modulation and HBV clearance .…”
Section: Viral and Immune Aspects Of Therapymentioning
confidence: 86%